Расчетная и опытная оценка результатов электротермического воздействия нормированного по международному стандарту IEC 62305-1-2010 импульса тока короткого удара искусственной молнии на тонкостенное покрытие из нержавеющей стали - Баранов, М.И.; Князев, В.В; Рудаков, С.В. (Електротехніка і електромеханіка, 2017)
Приведены результаты расчетной и опытной оценки электротермической стойкости тонкостенного покрытия наружной кровли высотного технического сооружения из нержавеющей стали марки 12Х18Н10Т к прямому воздействию на него нормированного по международному стандарту IEC 62305-1-2010 апериодического импульса тока искусственной молнии временной формы 10/350 мкс c амплитудой от 100 до 200 кА и заданными допусками на его амплитудно-временные параметры. Показано, что указанный импульсный ток молнии вызывает лишь локальное поверхностное термическое повреждение исследуемого стального покрытия при радиусе данной зоны повреждения не более 30 мм и глубине проплавления его стенки не более 50 мкм. Приведені результати розрахункової і досвідної оцінки електротермічної стійкості тонкостінного покриття зовнішньої крівлі висотної технічної споруди з неіржавіючої сталі мазкі 12Х18Н10Т до прямої дії на нього нормованого за міжнародним стандартом IEC 62305-1-2010 аперіодичного імпульсу струму штучної блискавки часової форми 10/350 мкс з амплітудою від 100 до 200 кА і заданими допусками на його амплітудно-часові параметри. Показано, що вказаний імпульсний струм блискавки викликає лише локальне поверхневе термічне пошкодження досліджуваного сталевого покриття при радіусі даної зони пошкодження не більше 30 мм і глибині проплавлення його стінки не більше 50 мкм. Purpose. Calculation and experimental researches of electrothermal resistibility of the pre-production thin-walled sheet models of outward roof of height technical buildings from stainless steel are easily soiled 12Х18Н10Т to direct action on them rationed by the International Standard IEC 62305-1-2010 aperiodic impulse of current of short bow of artificial lightning of temporal form 10/350 μs with the proper admittances on his peak-temporal parameters (PTP). Methodology. Electrophysics bases of technique of high voltage and large impulsive currents (LIC), and also scientific and technical bases of planning of high-voltage impulsive devices and measuring methods in them LIC with followings below extreme PTP: amplitude of impulse of current of ImL=200 кА (with admittance ±10 %); integral of action of impulse of current of JL=10·106 A2 ·s (with admittance ±35 %); %); duration of wavefront current of T1=10 μs (with admittance ±20 %); time, proper amplitude of impulse of current of ImL, tmL≤24 μs (with admittance ±20 %); duration of flowing of impulse of current of T2=350 μs (with admittance ±10 %). Results. The results of evaluation calculation and experimental researches of electro-thermal resistibility of the indicated preproduction sheet models are resulted measuring in the plan of 0,5 x 0,5 m from stainless steel are easily soiled the 12Х18Н10Т thickness of 1 mm to action on them of aperiodic impulse of current of short blow of artificial lightning with rationed PTP on the requirements of the International Standard IEC 62305-1- 2010. In high current experiments amplitude of ImL of the aperiodic rationed impulse of current of artificial lightning of temporal form of T1/T2=15 μs/315 μs changed in the range of (100- 184) кА. The integral of action of JL of impulse of current for IIV of levels of protection of lightning of technical objects (TO) numeral made from 2,32·106 А2 ·s to 7,88·106 А2 ·s, and the flowing through the probed pre-production steel models electric charge of qL numeral changed from 44,2 Kl to 81,3 Kl. It is shown that direct influence rationed by the International Standard IEC 62305-1-2010 impulse of current of short blow of artificial lightning with in-use PTP on the indicated preproduction steel models causes in them the rounded small hole of melting of surface of coverage a depth no more than 50 μm and diameter no more than 60 mm. The results of calculation and experiment coincide within the limits of 5 %. Originality. First in world practice on the unique generator of LIC of short blow of artificial lightning of type of GITM-10/350 experimental researches of electro-thermal resistibility of pre-production sheet models of outward roof are conducted TO of stainless steel 12Х18Н10Т is easily soiled to direct action on them of impulses of current of an artificial storm air spark digit with extreme parameters. Practical value. Drawing on the got results in practice of protection height TO from linear lightning will allow substantially to promote their functional and fire-prevention safety in the conditions of direct action on them of the plasma ductings of high current storm air spark discharge.